Case Report: Relapsed alveolar rhabdomyosarcoma treated with abemaciclib, temozolomide, and irinotecan in the JPCS study - Juan Ribelles, Antonio; Benavent, Nuria; Sanchez Mateos, Daniel; Pitou, Celine; Zhou, Yanhong; Hardebeck, Molly C.; Knoderer, Holly; Cañete, Adela (Frontiers in Oncology, 2025)
BackgroundCyclin-dependent kinase (CDK) 4 and CDK6 play fundamental roles in cell cycle progression. The CDK4/6 inhibitor abemaciclib, in combination with temozolomide and irinotecan, was evaluated in pediatric and young adult patients with relapsed/refractory solid tumors in the phase 1b dose-escalation study, JPCS Part A (NCT04238819). This case report describes the notable results of a patient with relapsed alveolar rhabdomyosarcoma (ARMS) who experienced a prolonged complete response.Case presentationAn 8-year-old White male was initially diagnosed with stage IV ARMS with PAX3-FOXO1 fusion. Molecular characterization following a fourth relapse revealed CDK4, ERBB3, GLI1, MYCN, and FGFR4 amplifications and MYCN mutation. After five relapses, the patient enrolled in JPCS Part A and received abemaciclib (55 mg/m2 twice daily continuously) in combination with temozolomide (100 mg/m2 daily) and irinotecan (50 mg/m2 daily) on days 1 to 5 of 21-day cycles. The patient received 12 cycles of the triplet combination, followed by 23 additional cycles of abemaciclib monotherapy. Complete response (CR) was achieved in less than 3 months, with a duration of response (DOR) of 22.6 months and progression-free survival (PFS) of 23.7 months. The study treatment was well tolerated.ConclusionCDK4/6 inhibition with abemaciclib in combination with temozolomide and irinotecan provided a durable response in a patient with heavily pretreated ARMS. Additional studies may be warranted to further understand the role of CDK4/6 inhibitors for treatment of ARMS.